Upaya Pemerintah Kota Samarinda Mewujudkan Good Governance Melalui Aplikasi Samarinda Santer - Sarliana Ramadhani; Letizia Dyastari (Jurnal Ilmu Pemerintahan, 2024)
This research will focus on examining the Samarinda City Government's efforts to realize good governance through the Samarinda Santer application as a whole in accordance with the mandate of Bureaucratic Reform, namely implementing good governance through the main indicators, namely accountability, transparency and efficiency. Good Governance is a form of government system where the road conditions can run cleanly, efficiently, openly and can fulfill everything that society needs. Governance is the mechanisms, practices, procedures of government for managing resources and solving public problems. The implementation of Good Governance in Indonesia began with the emergence of Law of the Republic of Indonesia Number 32 of 2004 concerning Regional Government Article 20 Paragraph 1 and was strengthened by Law of the Republic of Indonesia Number 14 of 2008 concerning Openness of Public Information so that the public can receive open public information regarding the administration of the State. everything that has an impact on the public interest. In dealing with maladministration in society, the Samarinda City government is trying to realize Good Governance through the Samarinda Santer Application. The Samarida City government's efforts to realize good governance through the Samarinda Santer application have three indicators used in its realization, namely accountability, transparency and efficiency.